Follow-up of COVID-19 recovered patients with mild disease - Alina Kashif (Nature Portfolio, 2021)
Abstract COVID-19 may manifest as mild, moderate or severe disease with each grade of severity having its own features and post-viral implications. With the rising burden of the pandemic, it is vital to identify not only active disease but any post-recovery complications as well. This study was conducted with the aim of identifying the presence of post-viral symptomatology in patients recovered from mild COVID-19 disease. Presence or absence of 11 post-viral symptoms was recorded and we found that 8 of the 11 studied symptoms were notably more prevalent amongst the female sample population. Our results validate the presence of prolonged symptoms months after recovery from mild COVID-19 disease, particularly in association with the female gender. Hence, proving the post-COVID syndrome is a recognizable diagnosis in the bigger context of the post-viral fatigue syndrome.